Fenomena Label Halal is it a Awareness or Branding - Arista Fauzi Kartika Sari; Junaidi Junaidi (Jurnal Ilmiah Ekonomi Islam, 2020)
The purpose of this study is to find out how to provide a "halal label" by producers for MSME products in Malang using ethnometodology. Ethnometodology is a research method that studies a practice or way. From the method of labeling halal, the motives of the producers will be known, whether the halal labeling is due to an Islamic awareness of halal products, or to attract market share. The research informant is the owner of MSME in Malang Raya. The results of this study are the indexicality of several producers illegally labeling halal, due to the halal belief in the food sold, and the official halal labeling from LPPOM MUI. Its reflexivity is the giving of halal labels because of the trust value of God and consumers, to increase sales, as well as the ethics of accountability to God and consumers.